The effect of particle size, location and season on the toxicity of urban and rural particulate matter. (20th November 2013) - Mirowsky, Jaime; Hickey, Christina; Horton, Lori; Blaustein, Martin; Galdanes, Karen; Peltier, Richard E.; Chillrud, Steven; Chen, Lung Chi; Ross, James; Nadas, Arthur; Lippmann, Morton; Gordon, Terry
Abstract: Particulate matter (PM) varies in chemical composition and mass concentration based on a number of factors including location, season, source and particle size. The aim of this study was to evaluate the in vitro and in vivo toxicity of coarse and fine PM simultaneously collected at three rural and two urban sites within the metropolitan New York City (NYC) region during two seasons, and to assess how particle size and elemental composition affect toxicity. Human pulmonary microvascular endothelial (HPMEC-ST1.6R) and bronchial epithelial (BEAS-2B) cell lines were exposed to PM (50 μg/mL) and analyzed for reactive oxygen species (ROS). Mice (FVB/N) were exposed by oropharyngeal aspiration to 50 µg PM, and lavage fluid was analyzed for total protein and PMN influx. The ROS response was greater in the HPMEC-ST1.6R cell line compared to BEAS-2B cells, but the responses were significantly correlated ( p  < 0.01). The ROS response was affected by location, locale and the location:size interaction in both cell lines, and an additional association for size was observed from HPMEC-ST1.6R cells. Urban fine PM generated the highest ROS response. In the mouse model, inflammation was associated with particle size and by a season:size interaction, with coarse PM producing greater PMN inflammation. This study showed that the aerodynamic size, locale (i.e. urban versus rural), and site of PM samples affected the ROS response in pulmonary endothelial and epithelial cells and the inflammatory response in mice. Importantly, these responses were dependent upon the chemical composition of the PM samples.